A qualitative assessment of nonclinical drivers of pediatric outpatient antibiotic prescribing: The importance of continuity. Issue 1 (29th June 2022) - Spencer, Hillary J. J.; Katz, Sophie; Staub, Milner; Audet, Carolyn M.; Banerjee, Ritu
Abstract: Background and objectives: Antibiotic overuse is common in outpatient pediatrics and varies across clinical setting and clinician type. We sought to identify social, behavioral, and environmental drivers of outpatient antibiotic prescribing for pediatric patients. Methods: We conducted semistructured interviews with physicians and advanced practice providers (APPs) across diverse outpatient settings including pediatric primary, urgent, and retail care. We used the grounded theory constant comparative method and a thematic approach to analysis. We developed a conceptual model, building on domains of continuity to map common themes and their relationships within the healthcare system. Results: We interviewed 55 physicians and APPs. Clinicians across all settings prioritized provision of guideline-concordant care but implemented these guidelines with varying degrees of success. The provision of guideline-concordant care was influenced by the patient–clinician relationship and patient or parent expectations (relational continuity); the clinician's access to patient clinical history (informational continuity); and the consistency of care delivered (management continuity). No difference in described themes was determined by setting or clinician type; however, clinicians in primary care described having more reliable relational and informational continuity. Conclusions: Clinicians described the absence of long-term relationships (relational continuity) and lack of availability of prior clinical history (informational continuity) as factors that may influence outpatient antibiotic prescribing. Guideline-concordant outpatient antibiotic prescribing was facilitated by consistent practice across settings (management continuity) and the presence of relational and informational continuity, which are common only in primary care. Management continuity may be more modifiable than informational and relational continuity and thus a focus for outpatient stewardship programs.